Knowledge among mothers regarding weaning practice of Jhangad community of Jhorahat V.D.C, Nepal (Our Nature, 2015)
The study was conducted among 50 mothers of Jhangad community to assess the knowledge regarding weaning practice on infant. Although the findings showed that most of the mothers had heard about weaning practice, only 76% mothers knew about ideal weaning  time. There was a difference between the time for the initiation of weaning and selection of the food items. 92% used  foods for weaning from local sources like rice and pulses (34%) because of its easy availability. A considerable number had a concept that proper weaning helps in overall growth and development of the child. 8% replied that it helps to prevent malnutrition. Health problems like diarrhoea were the most frequent problem complained by the mothers after weaning.DOI: http://dx.doi.org/10.3126/on.v12i1.12258Our Nature (2014), 12(1): 54-59